2020
DOI: 10.3390/en13112900
|View full text |Cite
|
Sign up to set email alerts
|

Water-Energy Management for Demand Charges and Energy Cost Optimization of a Pumping Stations System under a Renewable Virtual Power Plant Model

Abstract: The effects of climate change seriously affect agriculture at different latitudes of the planet because periods of drought are intensifying and the availability of water for agricultural irrigation is reducing. In addition, the energy cost associated with pumping water has increased notably in recent years due to, among other reasons, the maximum demand charges that are applied annually according to the contracted demand in each facility. Therefore, very efficient management of both water resources and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Inequality (26) determines upper and lower thresholds for the SoC. Equations (27) and (28) illustrate the rate of charging and discharging, respectively.…”
Section: Electrical Storage Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Inequality (26) determines upper and lower thresholds for the SoC. Equations (27) and (28) illustrate the rate of charging and discharging, respectively.…”
Section: Electrical Storage Systemmentioning
confidence: 99%
“…Higher energy use efficiency and lower energy costs are two main advantages of the approach. In Ref.,27 an energy management approach was suggested to integrate the flexibility potentials of water‐energy consumption into a virtual power plant. The study was successful in increasing the self‐consumption of renewable energy and decreasing electricity supply costs.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have also studied the possibility of integrating energy-water management systems into the overall grid. For example, in the PV system proposed in [9], with the constraint of minimizing the irrigation deficit, excess energy could be bought or sold to the overall grid, and a model was trained to minimize energy costs. Finally, in [10], a robust control approach was used to optimize the performance of a PV irrigation system connected to an overall grid, where the energy cost and irrigation deficit were minimized considering a worst-case scenario for the future price of energy from the grid.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches on the architecture of SPAPV have shown that, in order to improve the efficiency of water use, increase distribution uniformity and increase yield, at directly pumping systems [46], (that pump water only when PV captures solar radiation), water storage tanks [47], or accumulators (batteries) have to be added. The arrangements for localized irrigation with a water storage tank allow the administration of water to the plant when the energy generated by PV is not enough [48]. The SPAPV can be easily installed near the place of consumption, and the area occupied by PV can be optimized, which is why they are often used for irrigating tomatoes grown in solariums [49].…”
Section: Introductionmentioning
confidence: 99%